Multiple sclerosis clinical decision support system based on projection to reference datasets. Issue 12 (22nd November 2022) - Ed‐driouch, Chadia; Chéneau, Florent; Simon, Françoise; Pasquier, Guillaume; Combès, Benoit; Kerbrat, Anne; Le Page, Emmanuelle; Limou, Sophie; Vince, Nicolas; Laplaud, David‐Axel; Mars, Franck; Dumas, Cédric; et al.
Abstract: Objective: Multiple sclerosis (MS) is a multifactorial disease with increasingly complicated management. Our objective is to use on‐demand computational power to address the challenges of dynamically managing MS. Methods: A phase 3 clinical trial data (NCT00906399) were used to contextualize the medication efficacy of peg‐interferon beta‐1a vs placebo on patients with relapsing–remitting MS (RRMS). Using a set of reference patients (PORs), selected based on adequate features similar to those of an individual patient, we visualize disease activity by measuring the percentage of relapses, accumulation of new T2 lesions on MRI, and worsening EDSS during the clinical trial. Results: We developed MS Vista, a functional prototype of clinical decision support system (CDSS), with a user‐centered design and distributed infrastructure. MS Vista shows the medication efficacy of peginterferon beta‐1a versus placebo for each individual patient with RRMS. In addition, MS Vista initiated the integration of a longitudinal magnetic resonance imaging (MRI) viewer and interactive dual physician‐patient data display to facilitate communication. Interpretation: The pioneer use of PORs for each individual patient enables personalized analytics sustaining the dialog between neurologists, patients and caregivers with quantified evidence.